2012
DOI: 10.5388/aon.2012.12.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Health Behaviors and Health-Related Quality of Life among Breast Cancer Survivors

Abstract: Purpose:To examine the levels of physical activity (PA) and diet quality, socio-demographic and clinical correlates, and identify associations with health-related quality of life (HRQOL) among breast cancer survivors. Methods: The study used a cross-sectional study design. A total of 74 breast cancer survivors who had completed their primary cancer therapy were recruited from a comprehensive cancer center in Korea. Measurements used included the International Physical Activity Questionnaire, the Diet Quality I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that physical activity is effective not only in reducing psychological stress such as anxiety and depression [21], but also in preventing cancer, secondary cancer, and recurrence, and in increasing survival rates [22]. Notably, physical activity is the representative non-pharmacological method of managing stress and depression in cancer survivors, which is safe and practical and has a relatively low cost, and has been the recommended method [23]. Physical activity is generally known to increase the firing of serotonin neurons, facilitating the release and synthesis of serotonin to improve mood and reduce depressive symptoms [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that physical activity is effective not only in reducing psychological stress such as anxiety and depression [21], but also in preventing cancer, secondary cancer, and recurrence, and in increasing survival rates [22]. Notably, physical activity is the representative non-pharmacological method of managing stress and depression in cancer survivors, which is safe and practical and has a relatively low cost, and has been the recommended method [23]. Physical activity is generally known to increase the firing of serotonin neurons, facilitating the release and synthesis of serotonin to improve mood and reduce depressive symptoms [24].…”
Section: Discussionmentioning
confidence: 99%
“…A low level of serotonin is associated not only with depression but also with chronic pain, and the implications of such complex mechanisms can partially account for the results of this study, where the levels of stress and depression in cancer survivors were lower in those performing walking or muscle-strengthening exercise. A previous study showed that a shared finding is that depressive symptoms could be reduced by up to 50% or higher through exercise and physical activity, based on which it is recommended that an intervention of exercise be given to cancer patients as soon after cancer diagnosis as possible to lower depressive symptoms [23]. Further studies should also be conducted regarding numerous factors associated with exercise so as to effectively reduce rates of depression.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] However, a previous study reported that only 35.1% of breast cancer survivors performed the recommended amount of physical activity. [ 24 ] A recent study on preoperative older cancer patients reported that no physical complaints, information that was easy to understand, low-cost programs, and personal preference facilitated the performance of physical exercise. [ 25 ] However, it should be noted that older adults are more vulnerable to decline, particularly in physical functions, during and after cancer treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, CCS, who are more prone to developing chronic diseases and secondary cancer in the future, are known to be less or equally likely to be involved in unhealthy behaviors, compared with their healthy siblings (Chan et al, 2020). Health behaviors are also known to be an important factor affecting HRQOL in other populations, including elderly people with hypertension, breast cancer survivors, and general cancer survivors (Kim & Yun, 2012; Koh et al, 2019; Konjevoda et al, 2019; Li, Yu, et al, 2018). A few studies have examined the relationship between health behavior and HRQOL among CCS (Chan et al, 2020; Howell et al, 2018); however, to date, no such studies have been performed in Korea.…”
Section: Introductionmentioning
confidence: 99%